Pediatric rehabilitation : principles and practice - Alexander, Michael A. (Michael Allen), 1947-; Matthews, Dennis J.; Murphy, Kevin P., 1956- (Demos Medical Publishing, LLC, 2015)
Universally acknowledged as the cornerstone reference in the field, Pediatric Rehabilitation brings together renowned specialists from all sectors of the pediatric rehabilitation community to provide the most current and comprehensive information available. The fifth edition has been substantially updated and expanded with evidence-based discussions of new theories, therapies, interventions, research findings, and controversies. Five completely new chapters focus on such emerging areas as the use of ultrasound to guide motor point and nerve injections, rehabilitation of chronic pain and conve.